2022
DOI: 10.1007/s12012-022-09728-8
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption: A New Risk Factor for Arterial Stiffness?

Abstract: The relationship between alcohol consumption and cardiovascular disease risk is complex. Low-to-moderate daily alcohol consumption (1–2 drinks/day) is associated with reduced risk, whereas greater amounts of alcohol consumption and a “binge” pattern of drinking are associated with increased cardiovascular risk and mortality. Arterial stiffness may help explain the complex relationship. This integrated review summarizes data from studies examining the associations between alcohol consumption and pulse wave velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
3
8
0
3
Order By: Relevance
“…Indeed, the association between alcohol consumption and increased arterial stiffness remains unclear, with no association, J-shaped association or significant increased association or binge pattern of drinking. 42 In our study we found a significant relationship between alcohol consumption and increased arterial stiffness, with a threshold over 1.794 units/days. A recent study has shown that energy from alcohol (in calories) could be considered as a significant predictor of increased PWV.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Indeed, the association between alcohol consumption and increased arterial stiffness remains unclear, with no association, J-shaped association or significant increased association or binge pattern of drinking. 42 In our study we found a significant relationship between alcohol consumption and increased arterial stiffness, with a threshold over 1.794 units/days. A recent study has shown that energy from alcohol (in calories) could be considered as a significant predictor of increased PWV.…”
Section: Discussionsupporting
confidence: 53%
“…Nevertheless, two studies showed a dose‐response relationship between alcohol consumption and arterial stiffness in men 45,46 . A possible mechanism could be the effects of alcohol on lipids but this link remains unknown 42 . Alcohol can also induce changes in the arterial wall by degrading the eslatin induced by matrix metalloproteinase and enhancement of oxidative stress leading to vascular damages 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some mechanisms could explain this relationship. Alcohol consumption is associated with increased LDL and triglycerides and with decreased in HDL cholesterol 60 . Moreover, alcohol consumption is associated with the enhancement of the matrix metalloproteinase (MMP) leading to the degradation of the elastin in the vasculature wall 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated a U-shaped relationship [8,9], other studies had proposed a J-shaped correlation between atherosclerosis and alcohol intake [10][11][12][13]. There were also evidences which supported only heavy and sustained alcohol consumption was correlated with atherosclerosis [14,15]. This study intends to explore the relationship between pre-stroke alcohol consumption and the occurrence and degree of large cerebral stenosis in patients with rst acute ischemic stroke attack in 48 hours.…”
Section: Introductionmentioning
confidence: 94%